SPEECH CULTURE AS A FACTOR IN DEVELOPING COMMUNICATIVE COMPETENCE IN MODERN EDUCATION - Rayimjonova Umidaxon Yuldashevna (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract: This study explores the role of speech culture as a key factor in developing communicative competence in modern education. In the context of globalization and increasing digital interaction, effective communication has become essential for students’ academic success and social integration. The research aims to analyze the theoretical foundations of speech culture and identify effective pedagogical strategies for its development in educational settings. The study is based on qualitative methods, including comparative analysis of teaching approaches, observation of classroom communication, and evaluation of students’ oral and written performance. The findings indicate that speech culture enhances learners’ ability to express ideas clearly, logically, and appropriately in various contexts, while also fostering critical thinking and active participation. The research also identifies key challenges, such as declining reading habits, the influence of informal digital language, and limited opportunities for structured communication practice. To address these issues, the study recommends integrating interactive teaching methods, increasing communicative activities, and promoting adherence to language norms. The results demonstrate that systematic pedagogical approaches significantly improve communicative competence. Therefore, fostering speech culture should be considered a priority in modern education systems.